Freestyle race success in swimmers with intellectual disability - Daly, D. J.; Einarsson, I.; Van de Vliet, P.; Vanlandewijck, Y. (Biomechanics and Medicine in Swimming X, 2006)
Athletes with intellectual disability (ID) competing at international level show lower levels of explosive strength and cardiovascular fitness when compared to age matched trained persons. Behavioural characteristics such as motivation, and ability to deal with stress are more difficult to examine. In the 100-m freestyle race Paralympic competitors with loco-motor disability all use similar race speed and stroking strategies. But do trained and experienced swimmers with ID also generally adapt these patterns? Video race analysis data was collected on 81 elite male swimmers including ID athletes, loco-motor disabled, visually impaired as well as able bodied. In long course races there is a typical race pattern used by all swimmers with sufficient race experience regardless of absolute performance level. Individual race tactics do not generally determine the outcome.